Beyond fresh and direct: exploring the specialty food industry as a market outlet for small- and medium-sized farms. Issue 3 (23rd January 2018) - Feenstra, Gail; Hardesty, Shermain; Lev, Larry; Houston, Laurie; King, Robert; Joannides, Jan
Abstract: As small- and medium-sized farms struggle to remain viable in a competitive global economy, the expanding specialty food industry provides a potential marketing opportunity. These farms raise many of the farm products that can become the key ingredients in value-added foods. Little research exists about processed specialty foods made from locally/regionally sourced ingredients produced by small- and medium-sized farms. This study investigates the benefits, barriers and challenges for small- and medium-sized farmers who want to sell products to specialty food manufacturers (SFMs). This paper analyzes 240 survey responses from dairy, meat, fruit/vegetable/nuts and grain specialty manufacturers and 60 in-depth interviews of these manufacturers and farmers in California, Minnesota, Wisconsin, Washington and Oregon. We found that almost half of the manufacturers surveyed source primary ingredients directly from farms or from their own farm. More than half of the farms that supply these key ingredients are small or medium-sized, indicating that many farms in this category are already successfully supplying SFMs with key ingredients. The key benefits manufacturers receive from working with these farms included quality assurance, trust, and traceability. Key obstacles to such farmer/manufacturer transactions are: cost, inability to meet volume requirements, unreliable supply and lack of year-round supply. The nature of relationships between manufacturers and farmers emerged as a theme that influences the success of small- and medium-sized farms as ingredient suppliers. Whether they were large or small, most manufacturers purchased their key ingredients from multiple suppliers in order to reduce their risk. Overall, we find evidence that the specialty food industry is an emerging market channel for small- and medium-sized farms. We also find that to be successful suppliers of SFMs, farmers need to have processes in place to ensure the quality of their products; provide the specific attributes the manufacturer requires for its ingredients and be willing to communicate frequently with the manufacturer.